Codzienność hiszpańska drugiej połowy XVIII wieku w świetle korespondencji Johna i Sarah Jay - Stelmasiak, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2001)
The eighteenth century was the time of the big changes in Spain. At the beginning of the century the country was weak from political and economic point of view. Foreign travellers emphasized that Spain was depopulated and destroyed. „The age of reforms” started with the reign of Philip V. His successor Ferdinand VI continued the reconstruction. The main reforms were done during the reign of Charles III. He was the outstanding administrator in Spanish history. For American diplomats who came to Europe during the war of Independence Spain was very often the first point of their travels. America had great expectations of Spain, including large - scale aid and even an alliance. Seeing that the Congress decided to send a minister plenipotentiary to Spain in September 1779. This minister was John Jay. He was the most able and distinguished man whom the Congress could spare for this important mission. The article is based on John and Sarah Jay correspondence and it documents their adventures on the voyage to Spain in 1779. Then it shows the Jays’ opinions on Spanish everday life which they made during their stay in this country. John and Sarah Jay left America in October 1779 on the ship „Confederacy” . The stormy voyage was described in the letters of Sarah Jay too her mother because John Jay himself was too seasick to attend to formal correspondence. When the Jays’ arrived at Cadiz in February 1780 no one welcomed them. John Jay was accorded no offical status by the Spanish court. In March having sent William Carmichael (John Jay’s secretary) ahead, the Jays along set out for Madrid, four hundred miles away. The route to Madrid took them through Andalusia, La Mancha and Castile. As travellers, John and Sarah Jay brought their own food, they ate it with their own utensils, and they carried their own beds. They reached the capital in April 1780. Although the Jays rented the house in Madrid, John Jay was soon engaged in following the court form country seat to country seat. King Charles III moved very often from his winter capitol of El Pardo to Aranjuez and then to the north at the two sites of El Escorial and San Ildefonso. Moving the court from one palace to another made Spain one of the most expensive diplomatic establishment in Europe. That is why Sarah Jay stayed in Madrid most the time. Generally financial problems made their stay in Spain very difficult although John Jay was supported by Benjamin Franklin from Paris. To make matters worse from the beginning Jay’s mission was a hoples one. He had lowly status at the court and he felt lonely. He showed his discontent quite often in his letters. To sum up in the correspondence, John and Sarah Jay did not put a lot of attention to everyday life in Spain. There are a few letters where we can find fascinating descriptions of their ocean voyage, broken by near-disaster and the interlude a t Martinique, and then their arrived in Cadiz and their difficult overland journey to Madrid and the Spanish court.